Literature Review: Self-Confrontation in Family Nursing Therapy - Kartika Setia Purdani; Bachtiar Safrudin; Fiky Jayanti; Puji Lestari; Fachmi Alamsyah; Tsamarah Hanin Rana Fauziyyah; Wanda Amelia Nurhasanah; Nur Abida; Muhammad Kemal Ar Rifqi (International Journal of Health Engineering and Technology, 2026)
Family conflicts often arise due to low self-efficacy, differences in perception, and mismatched expectations between family members, which can trigger maladaptive behavior and reduce the quality of interpersonal relationships. One technique that nurses can use in their role as counselors to address these dynamics is confrontation, which is the process of helping individuals recognize discrepancies between their thoughts, feelings, and behaviors. This study aims to examine the effectiveness of confrontation techniques in counseling practice, specifically in the context of family nursing therapy. The method used was a literature review with an integrative approach to ten scientific articles published between 2017 and 2025. The literature search was conducted through Google Scholar and PubMed databases using the keywords confrontation, counseling, family, and adaptive behavior. The results of the study indicate that confrontation techniques have a positive impact on increasing self-awareness, emotional control, medication adherence, self-acceptance, and the quality of communication and relationships within the family. The effectiveness of this technique is greatly influenced by the counselor's or nurse's ability to apply confrontation empathetically, professionally, and non-judgmentally. It was concluded that confrontation techniques are an effective and adaptive counseling strategy in helping individuals and families develop more constructive behaviors and improve psychosocial well-being.